A general theory of magic - Mauss, Marcel (Oxon Routledge, 1972)
First written by Marcel Mauss and Henri Humbert in 1902, A General Theory of Magic gained a wide new readership when republished by Mauss in 1950. As a study of magic in 'primitive' societies and its survival today in our thoughts and social actions, it represents what Claude Lévi-Strauss called, in an introduction to that edition, the astonishing modernity of the mind of one of the century's greatest thinkers. The book offers a fascinating snapshot of magic throughout various cultures as well as deep sociological and religious insights still very much relevant today. At a period when art, magic and science appear to be crossing paths once again, A General Theory of Magic presents itself as a classic for our times.